Dielectric response on ultraviolet light irradiation of Ba 0.85 Ca 0.15 Zr 0.1 Ti 0.9 O 3 based ceramics - Panupong Jaiban (2019)
© 2019 Elsevier B.V. Ba 0.85 Ca 0.15 Zr 0.1 Ti 0.9 O 3 -based ceramics with doping of Ca 3 Co 4 O 9 , CaMn 0.98 Nb 0.02 O 3 , and Zn 0.98 Al 0.02 O were fabricated. CaO and CaCO 3 secondary phase were observed in all doped ceramics. These phases caused vacancies of Ca ions, which became associated with oxygen vacancies induced by ultraviolet light, leading to the formation of a defect dipole. The defect dipoles enhanced the photo-induced dielectric properties. The maximum enhancement was about 60% with Ca 3 Co 4 O 9 doping while other ceramics did not show significant change. The results here suggested that the ultraviolet light-induced dielectric properties of Ba 0.85 Ca 0.15 Zr 0.1 Ti 0.9 O 3 ceramic may be largely tunable by Ca 3 Co 4 O 9 addition and could be an alternative material for light sensors.